Physical Simulator for Colonoscopy: A Modular Design Approach and Validation - Martina Finocchiaro; Clara Zabban; Yu Huan; Alessandro D. Mazzotta; Sebastian Schostek; Alicia Casals; Albert Hernansanz; Arianna Menciassi; Alberto Arezzo; Gastone Ciuti (IEEE Access, 2023)
Simulators for gastrointestinal endoscopy offer the opportunity to train and assess clinicians’ skills in a low-risk and reliable environment. Physical simulators can enable a direct instrument-to-organ interaction not provided by virtual platforms. However, they present scarce visual realism and limited variability of the anatomical conditions. Herein, the authors present an innovative and low-cost methodology for designing and fabricating modular silicone colon simulators. The fabrication pipeline envisages parametric customization and development of 3D-printed molds for silicone pouring to obtain colon segments. The sizing of each colon segment is based on clinical data extracted by CT colonography images. Straight and curved segments are connected through silicone conjuncts to realize a customized and modular monolithic physical simulator. A 130 cm-long colon simulator prototype with assorted magnetically-connected polyps was fabricated and laid on a custom-made sensorized abdominal phantom. Content, face, and construct validity of the designed simulator were assessed by 17 endoscopists. In summary, this work demonstrated promising results for improving accessibility and flexibility of current colonoscopy physical simulators, paving the way for modular and personalized training programs.